The Impact of Corporate Governance, Financial Performance, Intellectual Capital and Enterprise Size on Integrated Reporting: Evidence from Ukraine - Vysochan, Oleh; Hyk, Vasyl; Vysochan, Olha (Journal of Environmental Accounting and Management, 2026)
The purpose of the study is to establish the impact of corporate governance, financial performance, intellectual capital and size of the enterprise on the quality of information disclosure in integrated reporting. The study used data from 30 large enterprises in various sectors of the economy of Ukraine, selected from annual financial statements, management reports and integrated reporting for 2018 and 2019, which are published and posted on their official websites. The statistical method of partial least square (PLS) data analysis in the computer program SmartPLS 3 was used to process the information. The results of the study showed that corporate governance, financial indicators, intellectual capital have a significant positive impact on integrated reporting, which did not confirm any dependence. The study conducted a comparative analysis of domestic and international research experience on the subject, identified issues and identified prospects for further development related to integrated reporting.